Estimation of stature from morphometric measurements of hand length and breadth - Mishra, Deepshikha; Shakya, Tripti; Pandey, Prabesh; Devbhandari, Ranjan Prasad (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Stature is an important element in identifying an individual, especially in cases where only fragmentary remains of the human body are available. Hand dimensions are useful in predicting stature. The aim of this study is to estimate stature using hand dimensions. The findings will be useful in estimating height in malformed bodies, bedridden patients, and in forensic investigations. Method: A cross-sectional study was conducted in 96 attendants of patient admitted in different wards of Patan Hospital, Patan Academy of Health Sciences. In this study stature, hand length and hand breadth was measured. Stature and the hand dimensions were compared across male and female applying t-test. Correlation of stature with various hand dimensions was assessed using pearson’s correlation coefficient. Linear regression was applied to see the relation of each of the hand dimensions and sex with stature, and multivariable linear regression was applied. Result: Stature was significantly higher in males than females, and all hand dimensions were larger in males, reflecting clear sexual dimorphism. Left hand length showed the strongest correlation to stature (r=0.658, p<0.001) and emerged as an independent predictor in multivariable analysis. Conclusion: This study confirms that hand dimensions, particularly left-hand length, are significant predictors of stature among adults in Nepal reinforcing the reliability of hand length as an anthropometric tool. The study contributes important baseline data for Nepal and highlights the practical application of hand measurements in both forensic and clinical contexts.